Motivation and Workload in Increasing Employee Performance of PT. Concorde Industry Karawang - Aprilia, Elpa; Jamaludin, Asep; Nandang, Nandang (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
The purpose of this research is to find out how workload and motivation influence the performance of PT employees. Concorde Industry Karawang. This research uses a quantitative approach and uses a causality survey method. The research population was 449 employees of PT Concorde Industry Karawang, and the sample used was a non-probability random sample. In this research, multiple regression, correlation, coefficient of determination, and hypothesis testing were used. The research results show that employee performance is influenced by motivation and workload simultaneously, and workload partially influences employee performance. It is proven that workload and motivation improve employee performance. The limitations of this research are limited to two influencing variables; further research should be carried out with more research variables. This research can be used by institutions to consider things that can improve the performance of their employees. It is hoped that further research will add to the company variables studied. This research investigates the motivation of PT employees. Concorde Industry Karawang, their workload, and their performance.